ASPECTS OF LEGAL REGULATION OF MILITARY AND DUAL-USE GOODS BLACK EXPORT - Sevostianenko, D. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The research on some aspects of legal regulation of military and dual-use goods black exports is carried out in the article. It is based on the analysis of modern views of scientists on the definition of "shadow market of military and dual-use goods", "black export of military and dual-use goods", "gray export of military and dual-use goods", as well as current legislation in relevant field. It is established that the smuggling process is not identical to the process of black export of military and dual-use goods, as the list of its items, as defined by Article 201 of the Criminal Code of Ukraine, is much smaller than the list of objects within the process investigated in the article and the inventory of which is stipulated by the state control over international transfers of military goods, approved by the Resolution of the Cabinet of Ministers of Ukraine of November 20, 2003 № 1807, as well as the Procedure for state control over international transfers of dual-use goods approved by the Cabinet of Ministers of Ukraine of January 28, 2004 № 86. The articles of the Criminal Code of Ukraine according to which actions within the process under consideration can be qualified are given, as well as the ways of improvement of the existing legislation, through modification of article 333 of the Criminal code of Ukraine that will allow to strengthen punishments for the made actions of the investigated process in the conditions of the special period state. The need for further research in the field of legal regulation of shadow markets for military and dual-use goods should be focused on gray exports, which will form a holistic picture of shadow markets for military and dual-use goods and form a single concept of their eradication.
Keywords: military-technical cooperation, military and dual-use goods, black export, smuggling, export control